Characterization analyses of MADS-box genes highlighting their functions with seed development in Ricinus communis - Sun, Jing; Zhou, Zekun; Meng, Fanqing; Wen, Mengyun; Liu, Aizhong; Yu, Anmin (Frontiers in Plant Science, 2025)
The MADS-box gene family plays a pivotal role in regulating floral organ development and various aspects of plant growth. Despite its well-established importance in many species, the function and evolution of MADS-box genes in Ricinus communis (castor) remain unexplored. This study presents an extensive genome-wide analysis of the MADS-box gene family in castor, covering their physicochemical characteristics, phylogenetics, gene architecture, chromosomal distribution, evolutionary dynamics, expression profiles, and co-expression networks. In total, 56 MADS-box genes were categorized into two main phylogenetic groups: type-I and type-II, which were further subdivided into three and two subgroups, respectively. Segmental duplication was found to be the primary driver of MADS-box gene expansion in castor, while purifying selection was evident across the entire gene family, as indicated by the Ka/Ks ratio. In-depth analyses of gene expression, promoter motifs, co-expression networks, and experimental validation (Y1H assays and qRT-PCR) revealed that RcMADS16 and RcMADS41 are key regulators of castor seed development, with RcMADS16 may involve in seed coat formation and RcMADS41 in oil accumulation. This study not only provides the first detailed insight into the evolutionary and functional landscape of MADS-box genes in castor, but also establishes a foundation for future investigations into the role of these genes in seed and organ development, both in castor and other plant species.